2018
DOI: 10.3389/fmicb.2018.01196
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biofilm Formation on the Persistence of Candidemia

Abstract: This study aimed to determine the predictors of persistent candidemia and examine the impact of biofilm formation by Candida isolates in adult patients with candidemia. Of the adult patients with candidemia in Kaohsiung Chang Gung Memorial Hospital between January 2007 and December 2012, 68 case patients with persistent candidemia (repeated candidemia after a 3-day systemic antifungal therapy) and 68 control patients with non-persistent candidemia (Candida clearance from the bloodstream after a 3-day systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…The presence of CVC is a prominent risk factor for PC; however, the timing of CVC removal is complex. The association between early removal of CVC and PC was not significant in our study, supported by another recent study 24 . Nucci et al 26 showed that early CVC removal had no effect on persistent or recurrent candidaemia or time to mycological eradication, although earlier studies have reported an association of improved outcome and faster mycological eradication with prompt CVC removal 27,28 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The presence of CVC is a prominent risk factor for PC; however, the timing of CVC removal is complex. The association between early removal of CVC and PC was not significant in our study, supported by another recent study 24 . Nucci et al 26 showed that early CVC removal had no effect on persistent or recurrent candidaemia or time to mycological eradication, although earlier studies have reported an association of improved outcome and faster mycological eradication with prompt CVC removal 27,28 …”
Section: Discussionsupporting
confidence: 85%
“…Catheter‐related infection was the most common source of infection in persistent cases. CVC has been demonstrated as a risk factor for PC in other studies as well 11,23‐25 . However, a recent cohort study conducted in adult patients did not find a significant association between CVC andPC 12 .…”
Section: Discussionmentioning
confidence: 91%
“…Candida species can also produce biofilm, considered as the most pathogenic trait, which result in treatment failures and recurrent infection [19]. It has also the ability to generate the filamentous form that is important to tissue invasion; however, these are dependent to environmental factors and type of species [2].…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion and biofilm production abilities of Candida spp. are among the principal risk factors for the development of invasive candidiasis [4][5][6]. Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical point of view, one of the most worrying characteristics of biofilms is their capacity to resist higher levels of antifungal drugs compared with planktonic cells. Hence, they are strongly associated with persistent candidaemia [6,8].…”
Section: Introductionmentioning
confidence: 99%